2015
DOI: 10.1128/jvi.00020-15
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Control of HIV-1 by Cytotoxic T Cells Specific for Multiple Conserved Epitopes

Abstract: Identification and characterization of CD8؉ T cells effectively controlling HIV-1 variants are necessary for the development of AIDS vaccines and for studies of AIDS pathogenesis, although such CD8 ؉ T cells have been only partially identified. In this study, we sought to identify CD8 ؉ T cells controlling HIV-1 variants in 401 Japanese individuals chronically infected with HIV-1 subtype B, in which protective alleles HLA-B*57 and HLA-B*27 are very rare, by using comprehensive and exhaustive methods. We identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
114
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(120 citation statements)
references
References 46 publications
5
114
1
Order By: Relevance
“…It is known that HLA-B*52:01-C*12:02 has a protective effect on the disease progression in HIV-1-infected Japanese individuals. Our recent study showed that HLA-B*52:01-restricted CTLs recognizing the five epitopes effectively suppress HIV-1 replication in the Japanese population (19). We showed here an additional mechanism for the protective effect of HLA-B*52:01-C*12:02 on the clinical outcome.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…It is known that HLA-B*52:01-C*12:02 has a protective effect on the disease progression in HIV-1-infected Japanese individuals. Our recent study showed that HLA-B*52:01-restricted CTLs recognizing the five epitopes effectively suppress HIV-1 replication in the Japanese population (19). We showed here an additional mechanism for the protective effect of HLA-B*52:01-C*12:02 on the clinical outcome.…”
Section: Discussionmentioning
confidence: 71%
“…We therefore sought to identify such CTL epitopes. We first attempted to identify a CTL epitope containing Pol 68 by using 11-mer Pol overlapping peptides generated in a previous study (19). Since HLA-B*52:01-binding peptides have the Q2 anchor residue (35), we selected two 11-mer overlapping peptides, Pol 11 to 30 (Pol11-30; ITLWQRPLVTI) and Pol11-31 (LWQRPLVTIKI) as candidate peptides.…”
Section: Resultsmentioning
confidence: 99%
“…There is growing consensus that not all of the antiviral immune responses contribute to immune control of the virus and that some clones directed against conserved epitopes may efficiently mediate viral clearance (12,13). Limitation of immune activation might therefore contribute to viral load control.…”
mentioning
confidence: 99%
“…Note that in each immunogen, the individual regions are in different orders to avoid possible induction of strong, but irrelevant, responses to potential junctional epitopes.
Figure 1Vaccines(A) tHIVconsvX immunogens (insets). The vaccines focus T cells on six highly functionally conserved regions of HIV-1 Gag and Pol proteins and their efficacy is enhanced by maximizing the vaccine match to global HIV-1 isolates through a computer-designed bivalent mosaic 47 and inclusion of beneficial epitopes 39, 40. For each immunogen tHIVconsv1-tHIVconsv6, the selected conserved regions are organized in different orders to avoid boosting of potential junctional epitopes.
…”
Section: Resultsmentioning
confidence: 99%
“…More recently, we enhanced this conserved-region approach by replacing the consensus sequences with a bivalent mosaic design (tHIVconsvX, second generation), 34 which computationally increases as much as possible the match of candidate vaccines to the currently worldwide circulating HIV-1 variants for maximum effector efficacy 34, 35, 36, 37, 38. Furthermore, we adjusted the boundaries of conserved regions to cover the majority of conserved and, at the same time, beneficial CTL epitopes, which have been associated in HIV-1-positive, treatment-naive cohorts on four continents with low viral load and high CD4 + T cell count 34, 39, 40. Finally, each of the six tHIVconsvX immunogens tHIVconsv1–tHIVconsv6 has the six conserved regions organized in a unique order to minimize induction of T cell responses to junctions, which are not present in the HIV-1 proteome and are, therefore, an avoidable distraction to the immune response 34 …”
Section: Introductionmentioning
confidence: 99%